Religion and women in India : Gender, faith, and politics 1780s-1980s - Sarkar, Tanika (New Delhi : Permanent Black, 2024)
In Religion and Women in India, Tanika Sarkar provides an account of gender prescriptions and proscriptions and their operation among various Indian religious communities, beginning with early British rule and concluding in the late twentieth century. Tracking various shifts and displacements in doctrinal thought and practice, she argues that Indian modernity was initiated largely through debates on gender, scripture, custom, and caste, which shaped ideal forms of masculine and feminine conduct. She demonstrates the organization of a modern public sphere around the controversies, cultural imaginaries, and political agitations over such issues as the age of consent, child marriage, widow remarriage, rape laws, and intercaste and interfaith relations. Gender norms are shown leaching into social attitudes, labor processes, and legal rights$1 (Bleading eventually to modern Indian feminism. Closely analyzing the interpenetration and co-constitution of religion, politics, and gender in India, while also comparing parallel developments in Pakistan and Bangladesh, this pioneering work offers a brilliant and synthesizing account of the battles between orthodoxy and its opponents over two hundred years. No historian, no feminist, no student of politics can afford to miss it.s
Keywords: Religion; Women; History